The impact of displacement on the social, economic and health situation on a sample of internally displaced families in Anbar Province, Iraq (Journal of Ideas in Health, 2019)
Background: Internally displaced people in Iraq are still suffering because the solutions were not radical. This study aims to assess the impact of displacement on the socio-economic, well-being, and mental health status of internally displaced families in Anbar province, Iraq.Methods:  A descriptive cross-sectional study was conducted from 3rd to 17th April 2017. Data was collected using a universal sampling technique. A total of 355 households interviewed with a modified questionnaire consisting of 26 close-ended questions related to the socio-economic, demographic, wellbeing, and mental health characteristics.Results: At the time of the study, about 55.5% of the surveyed displaced families have not returned home yet. Big families of more than seven members (59.4%) and residency in renting houses (82.8%) are two variables that may contribute to an economic burden. Mental health disorders such as depression and anxiety spread among 62.3% of surveyed families. Significant rise in chronic diseases from 64 (18.0%) cases before displacement to 102 cases (28.7%) after displacement. Few of them (21.6%) were able to access public health services. People who experienced violence are verbally abused at 52.1%. Lack of services (50.3%), the inability to repair the destroyed houses (26.4%), and the loss of houses due to complete destruction (23.3%) were the significant factors that inhibited families to return home back.Conclusion: Our findings indicate the need for urgent and strategic plans to improve the quality of logistics, health, and infrastructure services to motivate the displaced families to return back to their homes.
Keywords: internal displacement, families, household, conflict, mental health, Anbar, Iraq